(untitled) (Scientific journal of the Fergana State University, 2023)
In this article we are talking about the toponyms "Names of streets and makhallas of the city of Karshi", which have a special place in the study of toponymy of Uzbekistan, found in the Dictionary by Nafasov. A scientific evaluation of this work of the scientist devoted to the study of urban toponymy is given.